Late Holocene primary productivity and sea surface temperature variations in the northeastern Arabian Sea: Implications for winter monsoon variability. (7th August 2014) - Böll, Anna; Lückge, Andreas; Munz, Philipp; Forke, Sven; Schulz, Hartmut; Ramaswamy, V.; Rixen, Tim; Gaye, Birgit; Emeis, Kay‐Christian
Abstract Variability in the oceanic environment of the Arabian Sea region is strongly influenced by the seasonal monsoon cycle of alternating wind directions. Prominent and well studied is the summer monsoon, but much less is known about late Holocene changes in winter monsoon strength with winds from the northeast that drive convective mixing and high surface ocean productivity in the northeastern Arabian Sea. To establish a high‐resolution record of winter monsoon variability for the late Holocene, we analyzed alkenone‐derived sea surface temperature (SST) variations and proxies of primary productivity (organic carbon and δ15N) in a well‐laminated sediment core from the Pakistan continental margin. Weak winter monsoon intensities off Pakistan are indicated from 400 B.C. to 250 A.D. by reduced productivity and relatively high SST. At about 250 A.D., the intensity of the winter monsoon increased off Pakistan as indicated by a trend to lower SST. We infer that monsoon conditions were relatively unstable from ~500 to 1300 A.D., because primary production and SST were highly variable. Declining SST and elevated biological production from 1400 to 1900 A.D. suggest invigorated convective winter mixing by strengthening winter monsoon circulation, most likely a regional expression of colder climate conditions during the Little Ice Age on the Northern Hemisphere. The comparison of winter monsoon intensity with records of summer monsoon intensity suggests that an inverse relationship between summer and winter monsoon strength exists in the Asian monsoon system during the late Holocene, effected by shifts in the Intertropical Convergence Zone.